2014
DOI: 10.1007/s10554-014-0409-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iterative image reconstruction on CT-based calcium score measurements

Abstract: Iterative reconstruction techniques for coronary CT angiography have been introduced as an alternative for traditional filter back projection (FBP) to reduce image noise, allowing improved image quality and a potential for dose reduction. However, the impact of iterative reconstruction on the coronary artery calcium score is not fully known. In 112 consecutive stable patients with suspected coronary artery disease, the coronary calcium scores were assessed. Comparisons were made between the Agatston, volume an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
2
33
1
1
Order By: Relevance
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 94%
“…The effect of iterative reconstruction on quantitative measurements in cardiovascular imaging has been subject of recent studies [11][12][13][14][15][16][17][18]. One of the most commonly used cardiovascular risk assessment tools in CT is coronary calcium scoring (CCS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the kilovoltage was kept constant for the chest and cardiac CT for each patient and the same threshold was applied for both quantitative approaches. Lastly, we used iterative reconstructions for all reconstructions, while there are contradictory results on their influence on the absolute values of CAC scores [22][23][24][25]. This technical aspect was beyond the scope of our study and it requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the study by van Osch et al, our study had no patients with a score of 0 following HIR that had been > 0 in FBP. The number of patients with a score of 0 with ASIR increased by 13 % overall [13]. …”
Section: Radiation Dosementioning
confidence: 98%